PENGARUH PENGAWASAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA GROUND SUPPORT EEQUIPMENT (GSE) DI BANDAR UDARA INTERNASIONAL SULTAN HASANUDDIN MAKASSAR - Pratiwi, Sulfiana; Kusuma, Nur Makkie Perdana (Bhinneka Multidisiplin Journal, 2024)
AMC or Apron Movement Control Unit (AMC) handles supervision in the apron area. AMC performs important tasks such as carrying out surveillance activities, monitoring vehicle traffic, keeping the airside area clean, and recording flight data on the apron. The purpose of supervision of the apron movement control unit is to ensure that ground support equipment personnel work properly on activities in the apron area. This study uses a quantitative approach. Data collection was done through a questionnaire, which consisted of eleven people answering. Instrument tests such as validity and reliability, normality, multiple regression analysis, t, f tests, and coefficient of determination were used to analyze the data using spss 20. The results showed that the supervision variable (X1) did not affect performance (Y), with a value of 0.773 less than 0.05. The independent variable (X2) affects the dependent variable (Y), with a sig value of 0.049 less than 0.05. In addition, the variables of supervision (X1) and work discipline (X2) affect performance (Y), with a sig value of 0.000 less than 0.05